2021
DOI: 10.3389/fpsyg.2021.708361
|View full text |Cite
|
Sign up to set email alerts
|

Cognition-Mortality Associations Are More Pronounced When Estimated Jointly in Longitudinal and Time-to-Event Models

Abstract: With aging populations worldwide, there is growing interest in links between cognitive decline and elevated mortality risk—and, by extension, analytic approaches to further clarify these associations. Toward this end, some researchers have compared cognitive trajectories of survivors vs. decedents while others have examined longitudinal changes in cognition as predictive of mortality risk. A two-stage modeling framework is typically used in this latter approach; however, several recent studies have used joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(72 reference statements)
0
3
1
Order By: Relevance
“…In contrast, other factors, i.e. symptom severity, 44 cognitive functioning, [38][39][40]50 physical activity, 41 use of alcohol, illicit drug use, 51 and smoking 52 have been found to be related to both MD and mortality and the lack of information on those variables puts a limitation to the present findings.…”
Section: Discussioncontrasting
confidence: 66%
“…In contrast, other factors, i.e. symptom severity, 44 cognitive functioning, [38][39][40]50 physical activity, 41 use of alcohol, illicit drug use, 51 and smoking 52 have been found to be related to both MD and mortality and the lack of information on those variables puts a limitation to the present findings.…”
Section: Discussioncontrasting
confidence: 66%
“…This result could reflect that people who go out more and are active in finding their way are inevitably more exposed to potentially negative experiences in the environment, such as getting lost. Taken together, the result for years of education implies the need to promote lifelong learning, even in older age [66], to sustain spatial behaviors and thus navigation in the environment, which, in turn, promotes active aging. Regarding the role of gender, females reported going out less and not using navigation aids, such as maps and GPS, preferring the use of verbal directions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cognitive abilities, levels of and/or rate of change in memory, processing speed, or verbal fluency also predicted both risk of dying and/or being diagnosed with Alzheimer's disease (Ghisletta, 2008;Ghisletta et al, 2006;McArdle et al, 2005;Muniz-Terrera et al, 2011). Moreover, Aichele et al (2021) compared direct predictions from a JM to those of a two-step estimation procedure and showed that JM has greater power to estimate associations between cognitive decline and mortality in a large sample of adults. Based on these encouraging results in the health and cognitive literature, we therefore advocate that researchers consider JM a promising statistical tool to further the understanding of vulnerability processes throughout the life course.…”
Section: Joint Longitudinal and Survival Models To Study Vulnerabilit...mentioning
confidence: 99%